Cardioprotective effects of total and anthocyanin-rich extracts of Opuntia ficus-indica fruit on epinephrine-induced cardiac injury in rats - Leila Safaeian; Masoud Sadeghi-Dinani; Zahra Haghighatian; Mohammad-Bagher Fatahian; Marjan Khademizadeh (Asian Pacific Journal of Tropical Biomedicine)
Objective: To examine the effect of fruit extracts of Opuntia ficus-indica on epinephrine-induced myocardial injury in rats. Methods: Rats were pre-treated with hydroalcoholic and anthocyanin-rich extracts (250, 500, and 1 000 mg/kg) orally for 16 days. Epinephrine (2 mg/kg) was injected subcutaneously on days 15 and 16. Then ECG, heart rate, RR interval, cardiac histopathology, and serum parameters of cardiac damage and oxidative stress were evaluated. Results: Pretreatment with the hydroalcoholic and anthocyanin-rich extracts of Opuntia ficus-indica at doses of 500 and 1 000 mg/kg reversed epinephrine-induced changes in ECG, heart rate, RR interval, and cardiac histopathology, and attenuated creatine phosphokinase-MB activity and malondialdehyde level. The extracts at all doses diminished heart weight, lactate dehydrogenase, and aspartate aminotransferase, and also elevated total antioxidant capacity. However, 1 000 mg/kg of the anthocyanin-rich extract was more effective than the hydroalcoholic extract. Conclusions: Supplementation with fruit extracts of Opuntia ficus-indica, especially anthocyanin-rich extract, could protect against epinephrine-induced cardiac injury in rats by alleviating electrocardiographic, biochemical, histopathological, and oxidative stress parameters, and may be used in the treatment of cardiovascular diseases.